School of Romology at the University of Novi Sad: 2004-2015 - Denic, Slavica (Norma, 2026)
Although Romology is not formally taught as a distinct interdisciplinary subject at state universities in the Republic of Serbia, the School of Romology operated at the University of Novi Sad from 2004 to 2015 as an alternative educational platform. The program was designed to engage both Roma and non-Roma students, aiming to integrate the discipline into the broader academic environment. The curriculum employed an interdisciplinary approach to Roma studies, utilizing interactive methodologies such as discussion, mentoring, research, and project work. Furthermore, the program maintained networks with similar academic initiatives in Manchester and Graz. The aim of this paper is to present the School of Romology as a successful case study of higher education in an alternative academic space. It further argues for the necessity and benefits of institutionalizing Romology as a scientific discipline within Serbian faculties and universities. The empirical analysis is based on 43 evaluation forms completed by participants (2004-2015) and interviews with five former students. The study concludes that providing the Roma community with the opportunity to study their language, culture, and history is essential. It is recommended that similar or identical programs be re-established and sustained at higher education institutions within the University of Novi Sad.
Keywords: School of Romology; Roma community; academic community; higher education